2010
DOI: 10.1038/sj.bdj.2010.673
|View full text |Cite
|
Sign up to set email alerts
|

Coronectomy – oral surgery's answer to modern day conservative dentistry

Abstract: Removal of mandibular third molars is a common oral surgery procedure which is associated with a significant risk of injury to the inferior dental nerve (IDN). In an era of conservative dentistry the technique of coronectomy, which is conservative in terms of surgery and successful in minimising the incidence of IDN injury, has been met with some resistance and has been deemed non-ideal and controversial by many oral surgeons. This article outlines the benefits of coronectomy and highlights some examples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…The increased interest in coronectomy could be partly attributed to its applicability to treat patients with a high risk of injury to the inferior alveolar nerve or lower third molars associated with a dentigerous cyst. 33,34 Moreover, in recent years there have been more studies that have assessed the safety of coronectomy and randomized clinical trials that have evaluated the reduced risk to nerve injury by coronectomy. 3,[5][6][7]35 Two of the top 10 most cited coronectomy papers were randomized clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The increased interest in coronectomy could be partly attributed to its applicability to treat patients with a high risk of injury to the inferior alveolar nerve or lower third molars associated with a dentigerous cyst. 33,34 Moreover, in recent years there have been more studies that have assessed the safety of coronectomy and randomized clinical trials that have evaluated the reduced risk to nerve injury by coronectomy. 3,[5][6][7]35 Two of the top 10 most cited coronectomy papers were randomized clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Coronectomy or intentional root retention is associated with chances of infection due to retained pulp tissue [2,3,10] and is a controversial issue [10]. Also, the concept is relatively new, has no long term studies supporting it [10] and seems too conservative to the authors because of the concept of retaining a tissue which is indicated for removal.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, some operators resort to heroic attempts of removal, landing up with IAC damage, the management of which is confusing and uncertain [1]. Various other modalities have also been resorted to [2,3] in order to preserve the function of the inferior alveolar nerve (IAN) and varied outcomes have been reported in the literature [4].…”
Section: Introductionmentioning
confidence: 99%
“…Modern dentistry is based on conservative thinking and use of minimally invasive procedures 1 . In oral surgery, intentional partial odontectomy (coronectomy) could be an example of such a principle.…”
Section: Introductionmentioning
confidence: 99%